The role of institutional and reputational factors in the voluntary adoption of corporate social responsibility reporting standards - Nikolaeva, Ralitza; Bicho, Marta (Journal of the Academy of Marketing Science, 2011)
Firms are uncertain about the value of corporate social responsibility (CSR) reporting, which may involve significant costs. What makes them embark on the initiative? This is the first study to explore the voluntary adoption by companies of the world's most widespread framework of CSR reporting-the Global Reporting Initiative (GRI). The GRI case is impressive because it achieved its status in mere 10 years. The inquiry focuses on the role of the firm's institutional environment and identity communicators as drivers of the adoption of the GRI principles as a reputation management tool. The authors use a duration model to test hypotheses with data on 600 top global companies. The findings indicate that competitive and media pressures together with a company's CSR media visibility and CSR publicity efforts are important determinants of GRI adoption. Also, as the GRI framework becomes more institutionalized, companies pick up more information from prior adopters.